Естери багатоатомних спиртів — потенційні підсилювачі крізьшкірної проникності феназепаму - Бойко, Ю.О.; Кравченко, І.А.; Новікова, Н.С. (Актуальні проблеми транспортної медицини, 2010)
Было изучено влияние эфиров многоатомных спиртов на трансдермальную проницаемость кожи для феназепама in vivo. Изменения в подвижности и конформации липидных молекул рогового слоя было изучено с помощью метода ИК спектроскопии. Молекулярные механизмы текучести липосом, полученных из фосфолипидов и липидов рогового слоя, были изучены с помощью флуоресцентной спектроскопии. Нашими исследованиями показана эффективность использования сложных эфиров многоатомных спиртов в качестве усилителей чрезкож
ной проницаемости. Was studied the effect of polyatomic alcohols esters on the permeation of phenazepam from transdermal delivery system across skin in vivo. Changes in the amount and conformation of stratum corneum lipids were determined by Fourier transform infrared spectroscopy. Molecular level mechanisms of fluidity of large unilamellar phospholipids and lipids of stratum corneum vesicles were investigated by fluorescence spectroscopy. Our findings demonstrate that esters of polyatomic alcohols can be the effective enhancer of transdermal delivery.